2019
DOI: 10.1038/s41598-019-50803-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-motion perception is sensitized in vestibular migraine: pathophysiologic and clinical implications

Abstract: Vestibular migraine (VM) is the most common cause of spontaneous vertigo but remains poorly understood. We investigated the hypothesis that central vestibular pathways are sensitized in VM by measuring self-motion perceptual thresholds in patients and control subjects and by characterizing the vestibulo-ocular reflex (VOR) and vestibular and headache symptom severity. VM patients were abnormally sensitive to roll tilt, which co-modulates semicircular canal and otolith organ activity, but not to motions that ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 69 publications
(112 reference statements)
6
54
0
Order By: Relevance
“…Medial vestibular nucleus neurons are essential to the maintenance of vestibulo-ocular reflex, especially in stabilizing the images during head movement [58]. Clinical-based studies provide supporting evidence that ocular and perceptual thresholds are significantly increased in migraine patients with vestibular symptoms relative to those without vestibular symptoms, implying that sensitization of the medial vestibular nucleus might be a primary pathophysiological process underlying the vestibular hypersensitivity in migraine patients with vestibular symptoms [10,11]. Clinical trials investigating CGRP antibodies or CGRP receptor antagonists have shown statistically significantly efficacy for migraine treatment [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medial vestibular nucleus neurons are essential to the maintenance of vestibulo-ocular reflex, especially in stabilizing the images during head movement [58]. Clinical-based studies provide supporting evidence that ocular and perceptual thresholds are significantly increased in migraine patients with vestibular symptoms relative to those without vestibular symptoms, implying that sensitization of the medial vestibular nucleus might be a primary pathophysiological process underlying the vestibular hypersensitivity in migraine patients with vestibular symptoms [10,11]. Clinical trials investigating CGRP antibodies or CGRP receptor antagonists have shown statistically significantly efficacy for migraine treatment [45].…”
Section: Discussionmentioning
confidence: 99%
“…Whether vestibular symptom is one of clinical manifestations of central sensitization for migraine remains unproven. Clinical data demonstrated that patients with VM exhibited abnormally elevated vestibularocular threshold [10], as well as reduced roll tilt threshold [11] compared to migraine patients without vestibular symptoms and patients with a peripheral inner-ear disorder, indicating that dysfunction of the vestibular nuclei (VN) might be an underlying mechanism for vestibular symptoms in VM. As an important sensorimotor center in brainstem, VN and its direct connection with TNC had been demonstrated in rodents [12].…”
Section: Introductionmentioning
confidence: 99%
“…So, the cause of VM may be direct central activation of vestibular centres by the trigeminovascular system together with its effects on the inner ear [32]. It seems that vestibular symptoms come from the vestibular nuclei, which are simultaneously suppressed by inhibitory feedback from the cerebellar nodulus and uvula [33]. There is also evidence of otolithic pathway abnormalities in individuals with VM [34].…”
Section: Pathophysiology Of Vmmentioning
confidence: 99%
“…However, compensatory nystagmus and the subjective perception of rotation persist up to 30 s ( 34 , 43 , 203 ); this propagation of behavioral vestibular activity is accomplished through a mechanism called velocity storage [see ( 204 ) for a review on this topic but also see ( 205 , 206 ) for differing perspectives]. A reduced time constant (i.e., faster decay of nystagmus) has been identified in subjects with unilateral and bilateral vestibular loss ( 207 ), in those with central vestibular dysfunction ( 208 ), and in asymptomatic older adults ( 34 , 35 , 203 , 209 ).…”
Section: Introductionmentioning
confidence: 99%